Differential expression of an equivalent clonotype among BALB/c and C57BL/6 mice - Cancro, MP (The Rockefeller University Press, 1978)
The primary anti-phosphorylcholine (PC) response in BALB/c, C57BL/6, and congenic and recombinant inbred strains of these parental types has been examined in the splenic focus system. The frequencies of PC-specific precursors were shown to vary among these strains from 2 to 20 precursors per 10(6) splenic B cells. The distribution of these frequencies suggests that elements closely linked to or within the major histocompatibility complex may play a role in the determination of this parameter, although additional experiments are necessary to adequately assess this possibility. Moreover, all strains tested, regardless of immunoglobulin allotype, expressed monoclonal antibodies indistinguishable from the TEPC 15 myeloma protein (T15) clonotype. Further, the frequency of this clonotype in a given strain did not appear related to allotype, since both high and low T15 frequencies were found among strains of either the BALB/c (a(1)) or C57BL/6 (a(2)) allotype. The examination of normal serum for the T15 idiotype, however, revealed that only mice of the BALB/c allotype (a(1)) expressed the T15 idiotype in detectable quantities. After immunization with Diplococcus pneumoniae, sera from mice of the a(1) allotype consistently contained large quantities of the T15 idiotype, whereas sera from mice of the a(2) allotype exhibited various degrees of cross-reactivity with anti-T15 antibody. These results suggest that: (a) the allotype of an individual, although closely related to serum levels of an idiotype, is unrelated to the proportion of the precursor population which expresses that idiotype and; (b) the serum expression of a given idiotype may reflect regulatory processes, which act either during or before antigenic stimulation, rather than the actual clonotype representation in the repertoire. These findings indicate that distinctions must be made between the expression of idiotypic determinants within precursor B-cell populations and elements which regulate the subsequent appearance of those idiotypes in serum antibodies.